The Kampung Patin Model in Local Fisheries Development: Potential Policy Lessons for Southeast Asia - Ira Wulandari; Dina Mutmainnah; Nurwanti Nurwanti; Larassati Damayanti (Universitas Muhammadiyah Palembang, 2026)
The development of community-based inland aquaculture in Southeast Asia requires learning from local practices that successfully integrate production, institutional arrangements, value chains, and policy support. However, such practices need to be systematically assessed to identify principles that can be adapted to the ecological, social, institutional, and market contexts of other locations. This study assessed Kampung Patin in Kampar Regency, Indonesia, as a community-based inland aquaculture and value-chain practice with potential relevance for policy learning in Southeast Asia. A qualitative case-study design was applied through a purposive review of government documents, official publications, and academic literature. Nine indicators were examined: resources and commodities, policy governance, community institutions, value-chain integration, government support, economic sustainability, women’s participation, adaptive learning potential, and ecological sustainability. The findings showed strong performance in production, value-chain integration, policy support, and multilevel collaboration. Institutional capacity, economic resilience, and women’s participation remained uneven; adaptive learning potential was moderate, while ecological sustainability could not be assessed because case data were insufficient. Therefore, Kampung Patin is more appropriately understood as a documented local practice rather than as a model that can be directly replicated. Its regional value lay in principles that could be adapted to the ecological, institutional, market, and social conditions of recipient locations.